Ruminal pH and its relationship with dry matter intake, growth rate, and feed conversion ratio in commercial Australian feedlot cattle fed for 148 days. Issue 8 (14th April 2021) - Cusack, PMV; Dell'Osa, D; Wilkes, G; Grandini, D; Tedeschi, LO
Abstract : Objectives: Measurement of ruminal pH throughout a 148‐day feeding period in cattle fed commercial diets and to relate this to feed intake, growth rate and feed conversion ratio. Factors contributing to variation in rumen pH, including meal frequency, duration and weight, and, total daily intake, were also evaluated. Methods: Forty‐eight cattle were randomly allocated to two pens and 12 randomly selected from each pen had rumen pH monitoring boli inserted. Ruminal pH was measured every 10 min and feed intake was measured continually. The cattle were fed a commercial feedlot diet for 148 days and weighed into and out of the feedlot to measure growth rate and to calculate feed conversion ratio. Cattle from both pens were registered to collect individual feed intake data using the GrowSafe® feed management system. Results: Mean ruminal pH decreased with days on feed. Mean daily dry matter intake was the major contributor to greater average daily gain and lower ruminal pH. Lower mean ruminal pH was associated with greater average daily gain and lower feed conversion ratio, where it remained above the threshold of 5.6. There was no association between ruminal pH and average daily gain or feed conversion ratio for mean ruminal pH below 5.6. Conclusions: Ruminal acidosis can occur at any time during the feeding period, and the risk could be greater as days on feed increase. Feedlot production outcomes are not improved by ruminal pH depression below the threshold of 5.6.